QIYAS DALAM TINJAUAN HUKUM ISLAM - Fifi Hakimi; Wahidin Musta’in Billah (Institut Bisnis Muhammadiyah Bekasi, 2022)
The theory of qiyas has experienced very rapid development in this form in an abductive manner which previously was still in scope deductively, in the thought that it is regulated in Islamic law itself has external aspects in the concept of qiyas in the contemporary Islamic era, since the beginning, This qiyas is a theoretical matter that is always carried out by Islamic jurists, who conceptually have never experienced a change in dealing with problems that often arise in contemporary circles. It does not mean that it has limitations in looking broadly for illat which is theorized by qiyas law, and it is not limited to material concepts in concrete lines or contextually. However, the explanation given on any problem can be interpreted broadly and in detail to overcome it. Various questions and statements will be reviewed and solved as Islamic law regulates in aqidah.